Fracture toughness behavior of dissimilar metal (SA508 Gr.3 Class 1 and SA312 Type 304LN) weld joint: With and without stress relieving treatment. Issue 9 (11th June 2021) - Kumar, Suranjit; Kale, Rahul P.; Singh, Pawan Kumar; Ghosh, Mainak; Chattopadhyay, Jayanta
Abstract: Dissimilar metal welds (DMW) are used to connect the low‐alloy steel (LAS) pressure vessel and austenitic stainless steel (ASS) piping in nuclear power reactors. DMWs inherently have high gradient of carbon content across fusion boundary (LAS‐ASS), leading to carbon migration from LAS to ASS. Nickel‐based alloy is the preferred buttering and welding consumable to minimize carbon migration. Stress‐relieving treatment after buttering of LAS also enhances the carbon migration, which may lead to a reduction in local fracture toughness in heat affected zone (HAZ) of LAS. Therefore, this paper aims to study the effect of stress‐relieving treatment on the fracture toughness behavior of DMW. Fracture toughnesses of different zones of DMWs have been quantified in as‐welded and stress‐relieved conditions. It has been shown that stress‐relieving leads to lowering of fracture toughness with respect to as welded condition. This is attributed to increase in the microstructural heterogeneity in HAZ (LAS) and near fusion boundary of the DMW.